The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1039/b709856a
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor-beta signaling protects epidermal cytokine expression and immune function from UVB-induced impairment in mice

Abstract: A previous study in the hairless mouse, in which the photoimmune protective properties of a topical phytoestrogen or 17-beta-estradiol were abrogated by the estrogen receptor antagonist ICI 182,780, revealed that estrogen receptor (Er) signaling is involved in the regulation of the suppression of immune function by UVB (290-320 nm) radiation. Here we identify the expression of Er-beta but not Er-alpha mRNA in hairless mouse skin, whereas Er-alpha and Er-beta mRNA were present in normal haired mouse skin. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
32
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 25 publications
5
32
0
Order By: Relevance
“…c) . Although signaling through the estrogen receptor‐beta was protective in UV‐induced skin cancer , evidence showed that enhanced FOXP3 expression and Treg cell function were observed in pregnant, estrogen‐treated mice . George et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…c) . Although signaling through the estrogen receptor‐beta was protective in UV‐induced skin cancer , evidence showed that enhanced FOXP3 expression and Treg cell function were observed in pregnant, estrogen‐treated mice . George et al .…”
Section: Discussionmentioning
confidence: 99%
“…5c) (22)(23)(24)(25). Although signaling through the estrogen receptor-beta was protective in UV-induced skin cancer (26), evidence showed that enhanced FOXP3 expression and Treg cell function were observed in pregnant, estrogen-treated mice (24,25). George et al showed that UVA-treated mouse splenocytes could increase the frequency of FOXP3+ splenic T cells, after injected intravenously into syngeneic mice (27).…”
Section: Discussionmentioning
confidence: 99%
“…ER-β activation contributes to the down-regulation of HIF-1α and VEGF in the brain [12]. Furthermore, ER signaling is also involved in the suppression of immune function [33]. Our results show that the down-regulation of ER-β mRNA levels by compound 48/80 were inhibited by exposure to Buk music, indicating Buk music inhibited anaphylaxis by inhibiting the up-regulation of HIF-1α, VEGF, and TNF-α following ER-β activation.…”
Section: Discussionmentioning
confidence: 99%
“…Cho and colleagues performed a series of experiments suggesting a role for ERβ in UV-induced skin cancer. Expression of immunoprotective up-regulation of UVA-induced epidermal expression of interferon-γ and interleukin-12 (IL12) was inhibited in Erb -null mice as compared to controls (16). Erb -null mice exposed to UVB also exhibited enhanced expression of the immunosuppressive cytokine IL10 (16).…”
mentioning
confidence: 99%
“…Expression of immunoprotective up-regulation of UVA-induced epidermal expression of interferon-γ and interleukin-12 (IL12) was inhibited in Erb -null mice as compared to controls (16). Erb -null mice exposed to UVB also exhibited enhanced expression of the immunosuppressive cytokine IL10 (16). Using an ERβ antagonist or Erb -null mice, they also demonstrated that chemical antagonism of ERβ or genetic disruption of ERβ following irradiation with UV led to increased tumor growth that was due in part to altered immune function (17).…”
mentioning
confidence: 99%